Assessment of climate-based daylight performance in tropical office buildings : a case study - Chien, Szu-cheng (2014)
The utilization of daylight can significantly affect building performance, energy efficiency, productivity, as well as occupants' comfort and satisfaction in buildings. This paper aims to assess daylight performance for tropical office buildings in a parametric approach. Thus, four passive design categories are investigated, namely interior surface reflectance, glazing visual transmittance, light shelves and shading control. The approach is exemplified using the case study of two selected offices in Singapore. This study contributed to the assessment of the daylight performance and prediction of the consequences of retrofitting alternatives toward fostering the utilization of daylight in existing buildings in the tropics.